2021
DOI: 10.1177/09673911211009372
|View full text |Cite
|
Sign up to set email alerts
|

Green composites and their contribution toward sustainability: A review

Abstract: The current world environment scenario demands new and more eco-friendly solutions to global problems that cover the demands for materials. This sector has included green polymer-based composites and natural reinforcers from origins of renewable sources, these Green Composites (GC), natural-fiber-reinforced bio-composites in which the matrix is a bio-based polymer, have shown attractive characteristics. Biodegradability is one of the most important attributes for these new “green” materials, in that this chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 166 publications
0
18
0
1
Order By: Relevance
“…These both help increase the mechanical properties, facilitate degradability, and are antimicrobial. Plant fibers can be used to make ropes, textiles, mats, curtains, etc., which are eco-friendly and safe products (Vazquez-Nunez et al 2021 ). Microalgae biomass is another highly effective and eco-friendly material with a fast growth rate, the ability to produce high oil yield, and is the most effective way for heavy metal pollution (Yap et al 2021 ).…”
Section: Environmental/green Economiesmentioning
confidence: 99%
“…These both help increase the mechanical properties, facilitate degradability, and are antimicrobial. Plant fibers can be used to make ropes, textiles, mats, curtains, etc., which are eco-friendly and safe products (Vazquez-Nunez et al 2021 ). Microalgae biomass is another highly effective and eco-friendly material with a fast growth rate, the ability to produce high oil yield, and is the most effective way for heavy metal pollution (Yap et al 2021 ).…”
Section: Environmental/green Economiesmentioning
confidence: 99%
“…The application areas of green composites are extensive [91]. They can be used for environmental concerns and sustainability [92,93] or as construction materials [94]. The production of green composites can also be achieved with significantly different materials, as long as they are recyclable and biodegradable [95,96].…”
Section: Hybrid Biocompositesmentioning
confidence: 99%
“…[ 13,14 ] Also, it can be observed that the reinforcement of SCFs and SGFs purely enhances the mechanical properties of the thermoplastic composites, but underlying problems related to poor flame retardant characteristics remain a challenge. Given the importance of flame resistance performance in the modern composites market, [ 15 ] the need to introduce fillers which can both maintain the mechanical integrity and simultaneously improve the flame resistance property becomes significantly important. [ 16,17 ]…”
Section: Introductionmentioning
confidence: 99%